2020
DOI: 10.1177/1043659620919162
|View full text |Cite
|
Sign up to set email alerts
|

Socioecological Factors Affecting Fluid Restriction Adherence Among Korean Patients Receiving Hemodialysis: A Qualitative Study

Abstract: Introduction: To reduce morbidity and mortality rates, hemodialysis patients are advised to restrict their fluid intake. However, fluid restriction is the biggest stressor for the patients. This study explored the barriers and facilitators of fluid restriction among Korean hemodialysis patients. Method: This qualitative descriptive study was guided by the ecological model of health behavior. This study involved five focus group (23 patients) and individual interviews (4 patients) at two hospitals in Korea. Aud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 20 publications
0
16
0
1
Order By: Relevance
“…Previous studies indicated that younger hemodialysis patients are better able to accept and remember information about diet and fluid restrictions than older hemodialysis patients. However, attitudes toward fluid control behaviors may be negative due to hindrances in daily life, including work, delay of independence from parents, and decreased self-esteem (Kerklaan et al, 2020; Lee et al, 2021). In addition, younger hemodialysis patients typically have less pronounced physical symptoms, fewer complications, and better subjective health than do older patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies indicated that younger hemodialysis patients are better able to accept and remember information about diet and fluid restrictions than older hemodialysis patients. However, attitudes toward fluid control behaviors may be negative due to hindrances in daily life, including work, delay of independence from parents, and decreased self-esteem (Kerklaan et al, 2020; Lee et al, 2021). In addition, younger hemodialysis patients typically have less pronounced physical symptoms, fewer complications, and better subjective health than do older patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, young hemodialysis patients may fail to self-manage diet and fluid intake due to decreased self-confidence and social activity and this significantly were increased interdialytic weight gain (Bossola et al, 2013; Kerklaan et al, 2020). Although the 20 to 59 years age group had high knowledge of water restriction and low physiological symptom, lack of self-control, social relationships, social stigma, and Korean food culture had been the negative effect for behaviors of fluid restriction and diet (Lee et al, 2021). This leads to increased noncompliance with diet restrictions, resulting in increased interdialytic weight gain (López-Pintor et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The loss of employment opportunities leads to deterioration in one’s economic conditions, a decline in family and social status, and a lack of dignity. A previous study also showed that female patients’ high acceptance of disability could be related to their more frequent use of talk to dispel their negative emotions, seek solutions and thus gain more social support than men ( Lee et al, 2021 ).…”
Section: Discussionmentioning
confidence: 98%
“…These negative emotions lead to patients’ unwillingness to participate in social activities, low self-esteem and guilt toward their families ( Hagren et al, 2005 ). In short, the decline in physical function, the change in living environment and economic status and the emergence of psychological problems caused by long-term hemodialysis treatment make MHD patients prone to stigma ( Lee et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%